EXPERTS’ CONSENSUS ON THE INTERDISCIPLINARY APPROACH TOWARDS THE MANAGEMENT, DIAGNOSTICS, AND TREATMENT OF PATIENTS WITH METABOLIC SYNDROME (Кардиоваскулярная терапия и профилактика, 2013)
Experts’ consensus on the interdisciplinary approach towards the management, diagnostics, and treatment of patients with metabolic syndrome.